Краснолесье: стихи / Владимир Семакин - Семакин Владимир Кузьмич (Советская Россия, 1973)
Экземпляры: Аб (20240221) / Инвентарный номер: 122938 / Цена: 20.00 / Авт.знак: С 30 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)